A novel Ubc9 -dependent pathway regulates SIRT1- ER-α Axis and BRCA1- associated TNBC lung metastasis. Issue 4 (2017) - Xu, Jingyao; Shumate, Collin; Qin, Yulong; Reddy, Vaishali; Burnam, Yonte; Lopez, Victoria; Okoli, Joel; Reddy, E Shyam P; Rao, Veena N
No abstract available